Collaboration Between PAI Teachers and Class Homeroom Teachers in Shaping Character Honest and Religious at Elementary School 02 Sapan Sawahluto - Astuti, Astuti (Ruhama : Islamic Education Journal, 2024)
Collaboration is something that is needed in the successful achievement of planned goals, among the goals that every educational institution must achieve is the formation of student character. Therefore, this study aims to find and analyze the forms of collaboration carried out by Islamic religious education teachers with homeroom teachers at 02 Sapan Elementary School in shaping the honest character and religious character of students. The research was conducted with a qualitative approach, the data sources were Islamic religious education teachers, homeroom teachers and students selected by snowball sampling technique. Data were collected from informants using observation, interview and documentation study techniques. The results of this study are: First, the collaboration of Islamic religious education teachers and homeroom teachers in shaping honest and religious characters at Elementary School 02 Sapan is by instilling discipline to students to perform daily worship, avoiding students from lying to everyone; Second, the impact of the collaboration of Islamic religious education teachers and homeroom teachers is the realization of students who have honest and religious characters. Third, the inhibiting and supporting factors in shaping honest and religious characters at elementary school 02 Sapan are: lack of time, encouragement and cooperation from all resources at school. Keyword :Collaboration; Honest Character; Religious Character